PENGARUH BUDAYA ASING TERHADAP KEARIFAN BUDAYA MELAYU SAAT INI - Rohmah, Siti Mawadatur; Atika Maulidina; Dian Ratna Suri (LP2M Universitas Ibrahimy, 2025)
This research explores how digital media affects the use of the Malay language among youths in Bengkalis, Riau. Using qualitative methodology with interviews, observation, and digital content analysis, the research involved 23–30 active social media users aged 13–45 years. Findings reveal significant linguistic changes at lexical and syntactic levels, with extensive English borrowing and Indonesian slang becoming normative in digital communication among youth, while standard Malay use erodes. The study identifies negative impacts—including language attrition and cultural identity lossand positive opportunities for creative preservation through digital platforms. Digital media is not merely a threat but also presents avenues for innovative preservation when leveraged by youth. The study suggests community-based programs that empower young people to participate in language preservation, actively support government policies, and integrate digital literacy programs into educational institutions. This study advances understanding of language change in the digital age and offers useful guidance to communities seeking to strike a balance between modern communication and cultural heritage.